De trein - Simenon, Georges, 1903-1989; Romijn, K. H. (Utrecht : A.W. Bruna & Zoon, 1962)
Een radiomonteur verliest zijn vrouw en kind uit het oog wanneer ze in 1940 wegvluchten voor de Duitse troepen.